2017
DOI: 10.1002/pbc.26897
|View full text |Cite
|
Sign up to set email alerts
|

Computerized pediatric oncology prescriptions review by pharmacist: A descriptive analysis and associated risk factors

Abstract: Not surprisingly, PIs were predominantly to correct dose errors, half of which related to height and weight measurements that were not updated. No significant risk factors for errors were identified for errors except in the standardized status of prescription, which appears to be linked in part to our software that did not automatically reflect dose reduction from one course to the next. Medical double-checking followed by a clinical pharmacist's double check were effective in order to prevent prescription err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…e most frequently encountered DRPs were inappropriate dosing (high and low dose) followed by needs additional drug therapy and nonadherence to the prescribed medications. In line with this, several studies have also reported dosing problems (high and low dose) to be the most frequently (34.9%-61.8%) encountered DRPs in their settings [24,31,32]. e drugs more associated with dosing problems in this study included TMP/SMT, vancomycin, vincristine, metoclopramide, cimetidine, furosemide, and doxorubicin.…”
Section: Discussionsupporting
confidence: 74%
“…e most frequently encountered DRPs were inappropriate dosing (high and low dose) followed by needs additional drug therapy and nonadherence to the prescribed medications. In line with this, several studies have also reported dosing problems (high and low dose) to be the most frequently (34.9%-61.8%) encountered DRPs in their settings [24,31,32]. e drugs more associated with dosing problems in this study included TMP/SMT, vancomycin, vincristine, metoclopramide, cimetidine, furosemide, and doxorubicin.…”
Section: Discussionsupporting
confidence: 74%
“…Pharmacist-led intervention was a common practice for hospitalized patients worldwide, such as in Brazil [27] and France [28], but seldom performed for outpatients. Our study showed that pharmacist-led intervention also played an important role in ensuring drug safety for outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] They also outline the potential role of the pharmacist in an oncology setting; however, there was minimal reporting on the nature and incidence of actual or potential drug-related problems (DRPs) where targeted chemotherapy and/or immunotherapy was used to treat patients diagnosed with cancer. 13,14,[16][17][18][19][20][21] The pharmacist as a healthcare professional is actively involved in the identification of patients' treatment-related needs, verification of chemotherapy protocols, drug compounding, detection and prevention of adverse effects, and drug interactions in oncology settings. 22,23 It has been reported that the identification of DRPs by a pharmacist can help to improve patient adherence to drug treatment, treatment outcomes, and maintain or improve quality of life of patients receiving cancer treatment.…”
Section: Introductionmentioning
confidence: 99%